2022
DOI: 10.3390/catal12101234
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of Waste Biomass into Carbon-Supported Iron Catalyst for Syngas to Clean Liquid Fuel Production

Abstract: Syngas has been utilized in the production of chemicals and fuels, as well as in the creation of electricity. Feedstock impurities, such as nitrogen, sulfur, chlorine, and ash, in syngas have a negative impact on downstream processes. Fischer–Tropsch synthesis is a process that relies heavily on temperature to increase the production of liquid fuels (FTS). In this study, waste biomass converted into activated carbon and then a carbon-supported iron-based catalyst was prepared. The catalyst at 200 °C and 350 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…N was observed less as compared to pyrolysis P. MOF.N. ( Amin et al, 2022c ), ( Mahmood et al, 2022 )…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…N was observed less as compared to pyrolysis P. MOF.N. ( Amin et al, 2022c ), ( Mahmood et al, 2022 )…”
Section: Resultsmentioning
confidence: 90%
“…To determine the product selectivity, the peak area in the GCMS findings is employed. The FTS plant used for this experiment is shown schematically in Figure 2 ( Amin et al, 2022c ).…”
Section: Methodsmentioning
confidence: 99%
“…Promoters such as K and Cu have mostly been used to improve the activity and selectivity of iron-based catalysts [105]. Duan et al [106] found that the promotional effects of potassium on iron-based catalysts supported on carbon nanotubes include lower olefin selectivity, higher activity and better stability due to higher carbidisation and increased defects on carbon nanotubes to anchor the iron nanoparticles. For a K-promoted iron catalyst supported on carbon spheres, Xiong et al [57] reported that the addition of K led to higher hydrocarbon selectivity.…”
Section: The Role Of Promoters On Iron-based Catalysts During Auto-re...mentioning
confidence: 99%
“…Results reported in literature indicate that in order to obtain higher selectivity to C 5+ hydrocarbon chains, it is desirable to operate the process at 220 o C and a 2:1 H 2 /CO ratio. The work done by Amin et al [10]. showed that it was possible to achieve up to 72.6% of gasoline fraction and up to 80% of diesel fraction selectivity using an iron-based catalyst with potassium promoter at these conditions.…”
Section: Crimson Publishersmentioning
confidence: 99%